In Vivo Evaluation of the Ameliorating Effects of Small-Volume Resuscitation with Four Different Fluids on Endotoxemia-Induced Kidney Injury - Yan-ling Wang; Jing-hui Chen; Qiong-fang Zhu; Gao-feng Yu; Chen-fang Luo; Gang-jian Luo; Shang-rong Li; Zi-qing Hei (Mediators of Inflammation)
Acute kidney injury associated with renal hypoperfusion is a frequent and severe complication during sepsis. Fluid resuscitation is the main therapy. However, heart failure is usually lethal for those patients receiving large volumes of fluids. We compared the effects of small-volume resuscitation using four different treatment regimens, involving saline, hypertonic saline (HTS), hydroxyethyl starch (HES), or hypertonic saline hydroxyethyl starch (HSH), on the kidneys of rats treated with lipopolysaccharide (LPS) to induce endotoxemia. LPS injection caused reduced and progressively deteriorated systemic (arterial blood pressure) and renal hemodynamics (renal blood flow and renal vascular resistance index) over time. This deterioration was accompanied by marked renal functional and pathological injury, as well as an oxidative and inflammatory response, manifesting as increased levels of tumor necrosis factor-α, nitric oxide, and malondialdehyde and decreased activity of superoxide dismutase. Small-volume perfusion with saline failed to improve renal and systemic circulation. However, small-volume perfusion with HES and HSH greatly improved the above parameters, while HTS only transiently improved systemic and renal hemodynamics with obvious renal injury. Therefore, single small-volume resuscitation with HES and HSH could be valid therapeutic approaches to ameliorate kidney injury induced by endotoxemia, while HTS transiently delays injury and saline shows no protective effects.